The Concept Of Mitsaqan Ghalizhan In The Qur'ān and Hadith - Nada Putri Rohana (HUKUMAH: Jurnal Hukum Islam, 2024)
In Islam, building a family requires strong commitment, sincerity and readiness. Marriage is a strong agreement (mitsaqan ghalizhan). Advice on maintaining the integrity of marriage can be reviewed in the Al-Qur'an and hadith which are the basis of Islamic law. The research method uses descriptive studies processed from reading sources (literature review). Data sources use the Al-Quran and primary materials that support research. The data collection technique was carried out by tracing data sources relevant to the research through research studies, journals and articles about mitsaqan ghalizhan. The results of this research show that the essence of mitsaqan ghalizhan is not only about maintaining the integrity of the household to avoid divorce, but is also related to the purpose of marriage, namely sakinah, mawaddah, warahmah. The verses of the Qur'an and Hadith convey the crucial principle of the word mitsaqan ghalizhan, namely shaking the heavens, causing destruction and destroying humanity, if the agreement is betrayed and cheated. So, to maintain the strength of the agreement, you should think about the purpose and location first